"Falling down the Rabbit Fuck Hole": Spectacular Masculinities, Hypersexuality, and the Real in an Online Doping Community. (1st September 2022) - Andreasson, Jesper; Henning, April
Abstract: Through hegemonic ideas about muscles and extraordinary performances, image- and performance-enhancing drugs (IPEDs) and their use have been traditionally connected to hypersexualized masculinities. This link has resulted in spectacular ideas and fantasies about what IPEDs can do to/with men regarding their bodies and sexual performance. However, these ideas do not always manifest or correspond with daily life. Using a qualitative and case-study-based approach, this article investigates the relationship between doped and spectacular masculinities as they are presented and constructed in and through an online doping community, and users' experiences of side effects of the doped body and its social consequences. Analytically, the article draws on Guy Debord's work on the relationship between the spectacle and the real, and the ongoing theoretical debate on different reconfigurations and redefinitions of doped masculinities. It argues that anticipations of and effects from IPEDs can bring alternative ways of enacting doping masculinity and sexuality in the context of online communication while also blurring the lines between fantasy and lived experience.